Effects of High Oxygen Concentration on Driving Performance and Cerebral Hemodynamic Response - Kyu-Beom Kim; Soon-Cheol Chung; Byung-Chan Min (Tehnički Glasnik)
The positive effect of a high oxygen concentration on human cognitive ability for single tasks has been proven in various ways; however, few studies have investigated its effect on complex cognitive tasks. The aim of this study was to investigate the effect of a high oxygen concentration in driving situations that require complex cognitive abilities. The experiment was conducted in a laboratory equipped with a car simulator with 10 volunteer subjects. Driving was performed under normal and high-oxygen-concentration conditions. Various driving parameters and oxyhaemoglobin (HbO) levels in certain brain areas were measured during the experiments. The results show that vehicle velocity was maintained more consistently in the high-oxygen-concentration condition, and the HbO concentration increased (indicating greater activation) in the prefrontal and parietal cortices.